Sistem Informasi Geografis Tempat Kost Di Kota Palangka Raya Berbasis Website - Baghaskara, Ghiraldi; Putra, Putu Bagus Adidyana Anugrah; Pranatawijaya, Viktor Handrianus (Universitas Palangka Raya, 2022)
Currently the internet has become an important and effective means of communication to obtain various sources of information. The internet has also been proven to provide benefits to the community, one of which is in the business of providing residential services or boarding houses. Due to limited information about facilities, prices, locations and availability of boarding rooms, it is difficult for people to come directly to the location to survey the boarding house.The methodology used is Waterfall which has five stages, namely, Requirement Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, and Operation and Maintenance. At the analysis stage, data collection and needs analysis were carried out. At the design stage, Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD) are made. At the implementation stage, the system was created using PHP and JavaScript as the programming language, and MySQL as the database server. The testing method used is the Blackbox Testing method. Boarding seekers can view the location, route, boarding information, filter data, and see the panorama of the boarding house and can book a boarding house in the city of Palangka Raya. The boarding house owner can use this system as a place to promote his boarding house.